OVERWEIGHT/OBESITY IN COLLEGE STUDENTS: A SYSTEMATIC REVIEW - Barros, Gerleison Ribeiro (2022)
This article aims to characterize the prevalence and the factors associated with overweight/obesity in college students, through a systematic review. For doing so, the PRISMA protocol has been utilized. Articles about overweight/obesity were selected in college students on the databases of the National Library of Medicine (PUBMED), Scientific Electronic Library Online (SciELO), Biblioteca Virtual em Saúde (BVS), Web of Science and Scopus, it was considered the publication period from 2014 to 2019. We found 4,740 articles and 28 met the eligibility criteria. The overweight/obesity prevalence in college students varied from 9.5% to 47.0%. The Odds Ratio was the most used association measure (comparison) in studies. As characteristics that favor overweight/obesity, inadequate diet, income, male gender, low level of physical activity and family history of overweight/obesity are mentioned. The factors associated with protection against overweight/obesity were a healthy diet, regular physical activity and screen time. Finally, this review showed that university students are prone to overweight/obesity, as they have behavioral factors related to inadequate diet, low level of physical activity, income, being male, and sociocultural and family aspects due to a history of overweight/obesity. In counterpart, this review argues that healthy diet and physical activity and reduced screen time represent a health maintenance factor against overweight/obesity.